Microsoft certified application specialist (MCAS) - Matson, Lauri; Safari eBooks ([S.l.] : Virtual Training Co., 2005)
"Microsoft Office is the foundation of most business computer systems; understanding its power and utilizing its productivity is crucial in today's environment. The Microsoft Certified Application Specialist (MCAS) certification is a series of performance-based exams of the Microsoft Office Suite. The exams focus on the use of these programs in a "real world" enviroment: Microsoft Office Word 2007, Excel 2007, PowerPoint 2007, Access 2007, Outlook 2007, and Windows Vista. Acquiring MCAS Certification places a candidate above the rest when searching for new positions and advancement opportunities. This course prepares you for MCAS exams 77-600 through 77-605 by teaching the skills you need to master in each of the programs to achieve the highest standards of performance and efficiency. To begin learning today, simply click on the movie links." --Resource description page.
Title from resource description page (viewed Aug. 1, 2011).
Keywords: Microsoft Office -- Examinations -- Study guides; Business -- Computer programs -- Examinations -- Study guides; Word processing -- Examinations -- Study guides; Electronic spreadsheets -- Examinations -- Study guides; Integrated software -- Examinations -- Study guides; Electronic books